1994
DOI: 10.1002/jcp.1041580104
|View full text |Cite
|
Sign up to set email alerts
|

Iron absorption by CaCo 2 cells cultivated in serum‐free medium as in vitro model of the human intestinal epithelial barrier

Abstract: A cell culture system consisting of confluent monolayer of human enterocyte-like CaCo 2 cells, cultivated in a serum-free nutritive medium, on microporous synthetic membranes has been used as an in vitro model of the intestinal epithelial barrier. The uptake of 55ferric citrate, as well as the transepithelial passage from the apical to the basolateral pole, have been studied. CaCo 2 cells accumulate iron in a time- and concentration-dependent process, largely specific from the apical pole. When 55ferric citrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 45 publications
0
26
1
1
Order By: Relevance
“…HepG2 cells are derived from a human hepatoblastoma and retain many of the differentiated features of mature hepatocytes (9). CaCo-2 cells are derived from a human colon carcinoma and have been a useful model for the study of intestinal epithelial function (10)(11)(12)(13). MDCK cells are derived from distal tubular cells of a canine kidney which exhibit polarized functions (14,15), Cos-1 cells, derived from kidney of a monkey, exhibit fibroblast-like characteristics, and HeLa cells are derived from a human cervical carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…HepG2 cells are derived from a human hepatoblastoma and retain many of the differentiated features of mature hepatocytes (9). CaCo-2 cells are derived from a human colon carcinoma and have been a useful model for the study of intestinal epithelial function (10)(11)(12)(13). MDCK cells are derived from distal tubular cells of a canine kidney which exhibit polarized functions (14,15), Cos-1 cells, derived from kidney of a monkey, exhibit fibroblast-like characteristics, and HeLa cells are derived from a human cervical carcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…4,6 In our laboratory, we use microporous membranes obtained by a track-etching process which allows the preparation of capillary-pore' membranes 57 with very uniform, nearly perfectly round cylindrical pores. Such membranes are made from homogeneous 10±20 mm thick polymer ®lm precursors in two steps, consisting of bombardment with heavy ions (Ar +9 ) accelerated in a cyclotron, followed by immersion into an appropriate solution of reagents which preferentially etches the tracks, leading to the creation of pores.…”
Section: Surface Chemistrymentioning
confidence: 99%
“…The aqueous phase was extracted with ethyl acetate (4Â150 mL). The organic phases were dried over MgSO 4 …”
Section: Experimental Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of iron taken up by cells was calculated from the specific radioactivity of the test solution and is presented as pmol/insert (Halleux & Schneider, 1994;Han et a/, 1995). showed that the iron uptake increased by more than 50% when the molar ratio of Fe3+ : NTA was decreased from I : 2 to I : 1.…”
Section: Yasumotomentioning
confidence: 99%